Potret Industri Halal Indonesia: Peluang dan Tantangan - Muhammad Anwar Fathoni (ITB AAS INDONESIA Surakarta, 2020)
This study aims to explain the positioning of the Halal Industry in Indonesia. This study also identifies opportunities and challenges in its development. The method used in this study is a descriptive-qualitative method with a phenomenological approach. The data obtained were analyzed using qualitative analysis through data reduction, categorization, and verification. This research found that Indonesia has the potential to develop the Halal Industry in various sectors, especially halal food, halal travel, halal fashion, and halal finance. The development of the Halal Industry also has the potential to increase national economic growth. However, Indonesia must face various challenges such as the low halal awareness, low local product competitiveness, and problems in implementing the Halal Product Guarantee Regulation.